2012
DOI: 10.5194/hessd-9-7801-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated global water mapping based on wide-swath orbital synthetic aperture radar

Abstract: This paper presents an automated technique, embedded in an online service, which ingests orbital synthetic aperture radar (SAR) imagery and outputs surface water maps in near real time and on a global scale. The service anticipates future open data dissemination of water extent information using the European Space Agency's Sentinel-1 data. The classification methods used are innovative but practical and different per 1 × 1 degree tile. For each tile, a probability distribution function of a pixel, being covere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A representative index in the drainage based group is the Height Above Nearest Drainage (HAND) index, which was presented by Rennó et al [27] and implemented by Nobre et al [28]. This index also attracted a lot of attention and has been applied in many water detection studies [5,[29][30][31]. This study aims to conduct a comprehensive comparison on MrVBF and HAND indices, especially on their ability to assist surface water mapping using Sentinel-1A dual-polarized SAR data.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative index in the drainage based group is the Height Above Nearest Drainage (HAND) index, which was presented by Rennó et al [27] and implemented by Nobre et al [28]. This index also attracted a lot of attention and has been applied in many water detection studies [5,[29][30][31]. This study aims to conduct a comprehensive comparison on MrVBF and HAND indices, especially on their ability to assist surface water mapping using Sentinel-1A dual-polarized SAR data.…”
Section: Study Sitesmentioning
confidence: 99%
“…Synthetic Aperture Radar (SAR) sensors have been widely applied in detecting and monitoring water bodies due to their suitable spatial resolution, as well as the ability to penetrate cloud and vegetation cover [5,6]. Until recently, SAR sensors had a relatively low temporal frequency (about 24-35 days for acquisitions in the same geometric configuration) [7], which hinders the intensive monitoring of surface water variation.…”
Section: Introductionmentioning
confidence: 99%
“…Water monitoring using Synthetic Aperture Radar (SAR) has been the object of study for many researchers [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Due to its all-weather capabilities, and its image acquisition capacity during day or night or in cloudy conditions, SAR imagery offers better alternatives for water mapping than optical imagery [5].…”
Section: Introductionmentioning
confidence: 99%
“…Segmentation algorithms are quite successful but computationally expensive. In many cases, statistical information is combined with digital elevation models [8,14,16], where pixels likely to contain water are first determined based on topographic data and the probability of water is based on histograms of water vs. land pixels in the image, but this requires a coarse water mask to determine the statistics of water pixels. This dependence on a pre-determined water mask and high-resolution digital elevation models makes these methods unusable for mapping small ephemeral water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that SAR images acquired at the higher C-band frequency can also be used for detecting floods in less vegetated areas e.g., [14][15][16][17]. SAR images acquired in Wide Swath (WS) mode by the Advanced SAR (ASAR) onboard ENVISAT, at a spatial resolution of 150 m, were widely used for the monitoring of flood dynamics from local to regional scales [16][17][18][19]. Only 29 ASAR images were acquired in WS mode between November 2002 and March 2012 and just 14 during the rainy seasons due to acquisitions in other modes.…”
Section: Introductionmentioning
confidence: 99%